The Current Application and Future Prospects of Astragalus Polysaccharide Combined With Cancer Immunotherapy: A Review - Kong, Fanming; Chen, Tianqi; Li, Xiaojiang; Jia, Yingjie (Frontiers in Pharmacology, 2021)
So far, immunotherapy has been shown to have impressive effects on different cancers in clinical trials. All those immunotherapies generally derived from three main therapeutic approaches: immune checkpoint inhibitors, immune cell vaccination and adoptive cellular immunotherapy. Our research systematically reviewed a wide range of clinical trials and laboratory studies of APS, elucidated the potential feasibility of using APS in activating adoptive immunotherapy. Apart from being effective in adaptive “passive” immunotherapy such as LAK treatment and DC-CIK treatment, APS could also regulate the PD-1/PD-L1 on the surface of the immune cells, as a part in the immune checkpoint inhibitory signaling pathway by activating the immune-suppressed microenvironment by regulating cytokines, TLR4, NF-κB, and MAPK pathways, immune cells such as DCs, macrophages, NK cells and so on. In view of the multiple functions of APS in immunotherapy and TME, combination of APS and immunotherapy in cancer treatment has a promising prospect.